Bringing the R Back to SBAR: A Focused Heart Failure SBAR Tool. Issue 3 (August 2019) - Leonard, Christina; Zomorodi, Meg
This article describes a quality improvement (QI) project implemented in a home health setting among a population of patients with heart failure (HF). It was discovered there was a lack of nurse-led recommendations and ineffective use of the situation, background, assessment, and recommendations (SBAR) tool among home health nurse when communicating with providers about HF patients. Therefore, the QI project focused on creating and implementing a focused HF SBAR tool and a self-care patient checklist to be utilized by all home health nurses for all visits with HF patients. The focused HF tool was created and laminated and became part of home health nurse's identification badges. The implementation phase took place over a 60-day time period. Following implementation, outcomes were measured and demonstrated an increased use of SBAR, and an increase in nurse-led recommendations documented. In addition, there was a decrease in acute hospitalizations for HF among home health patients. Furthermore, there was an increase in nurse-led interventions implemented in the home along with an increase of referrals to physical therapy (PT) and occupational therapy (OT). The educational session was well-received and prompted a practice change in the delivery of future continuing education content. Finally, organizational leadership reported increased confidence and improved interprofessional communication among home health nurses and providers.